2020
DOI: 10.1371/journal.pone.0230208
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic aortic graft replacement of the ascending thoracic aorta alters biomechanics of the native descending aorta as assessed by transthoracic echocardiography

Abstract: The funders had no role in study design, data collection and greater wall thickness, and higher prevalence of calcific atherosclerotic plaque in the degenerative group (all p<0.05). In multivariate analysis, congenital/genetically associated AA etiology conferred a 4-fold increment in magnitude of augmented native descending aortic strain after proximal grafting (B = 4.19 [CI 1.6, 6.8]; p = 0.002) independent of age and descending aortic size. Conclusions Prosthetic graft replacement of the ascending aorta inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…These findings are consistent with expectations based on prior comparisons of regional differences in elastic fiber deterioration ( 33 ) and wall mechanics ( 34 ) along the length of the Fbn1 mgR / mgR aorta. Of clinical importance, longitudinal studies in patients have revealed that the descending thoracic aorta presents with increasing aortopathy following surgical repair of the proximal aorta in Marfan patients ( 35 ). Although it is not known whether this increased risk arises because of changes in hemodynamic loading on the descending thoracic aorta following the surgical implantation of a stiff synthetic proximal graft or simply whether surgical extension of life-span allows a longer period for the descending segment to deteriorate, the importance of studying the descending aorta is nevertheless clear.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with expectations based on prior comparisons of regional differences in elastic fiber deterioration ( 33 ) and wall mechanics ( 34 ) along the length of the Fbn1 mgR / mgR aorta. Of clinical importance, longitudinal studies in patients have revealed that the descending thoracic aorta presents with increasing aortopathy following surgical repair of the proximal aorta in Marfan patients ( 35 ). Although it is not known whether this increased risk arises because of changes in hemodynamic loading on the descending thoracic aorta following the surgical implantation of a stiff synthetic proximal graft or simply whether surgical extension of life-span allows a longer period for the descending segment to deteriorate, the importance of studying the descending aorta is nevertheless clear.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings extend upon prior studies which have demonstrated the utility of echo and CMR in assessing characterizing aortic physiology in surgical populations and predicting clinical outcomes in cardiovascular disease 9,15‐17 . For example, Rong et al demonstrated that surgical AA graft replacement increases immediate circumferential strain of the descending aorta, suggesting that surgical grafts augment energy transfer to the distal aorta and may contribute to progressive distal aortic dilation or dissection after surgery: Subsequent data demonstrated increased descending aortic strain to be sustained among ambulatory patients undergoing transthoracic echo prior to and following AA graft replacement 5 . Scarabello et al evaluated AA strain using CMR in a large diverse cohort and found that significant differences in age, gender, and cardiovascular disease independently affected AA strain 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous literature by our group and others, 5,7‐9 the following global indices of aortic biomechanics were considered for both TEE and CMR analysis: Global circumferential aortic strain (GCS)—peak circumferential deformation of the aortic wall between systole and diastole (measured as the relative (%) difference between these two time points; [end‐systole−end‐diastole]/end‐diastole × 100). Pulse pressure–adjusted GCS—GCS normalized for pulse pressure (PP): (GCS/PP) 9 Time‐to‐peak (TTP) strain—calculated as time interval between initial LV systolic contraction (R wave) and maximal circumferential aortic strain. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies to identify which patients would benefit from surgery is critical since an operation is not without risks. Ascending aorta replacement grafts are stiff with altered geometry, which can lead to downstream descending aorta distention and aneurysm (86). Presently, prophylactic surgery for aortic dilatation is guided by aortic diameter and presence of risk factors that would predispose one to aortic complications (85).…”
Section: Clinical Implications Of Bicuspid Aortopathymentioning
confidence: 99%